The Transformative Power of Information and Communication Technology in Empowering Women in Afghanistan - Hakimi, Musawer; Quchi, Mohammad Mustafa; Hasas, Ansarullah; Fazil, Abdul Wajid (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. This research addresses the intersection of Information and Communication Technology (ICT) and women’s empowerment in Afghanistan, aligning with global initiatives and Sustainable Development Goals (SDGs). The study aims to provide nuanced insights into the multifaceted impact of ICT on financial independence, economic empowerment, and health outcomes among Afghan women. Purpose. The research employs a purposive sampling method, involving 170 participants from diverse regions in Afghanistan to ensure representation from areas with varying socio-economic and cultural characteristics. Through a mixed-methods approach, including structured surveys and qualitative analysis, the study seeks to understand the perceptions of ICT and its experiences with women’s empowerment. Method. Structured surveys cover demographics, ICT perceptions, and women’s empowerment experiences. Qualitative data undergo thematic analysis, while quantitative analysis utilizes statistical methods such as ANOVA, logistic regression, chi-square tests, binomial tests, and descriptive statistics. Results. The findings underscore a consensus among participants on the positive impact of ICT, particularly on financial independence, economic empowerment, and health outcomes. Associations between telemedicine, digital health, and improved women’s health are identified. Binomial tests highlight success in bridging the digital gender gap and enhancing awareness. Positive perceptions of social media, online communities, and digital advocacy in promoting gender equality are revealed through descriptive statistics. Conclusion. This study contributes novel insights by comprehensively examining the impact of ICT on women’s empowerment in Afghanistan, covering diverse dimensions such as financial independence, economic empowerment, and health outcomes. The robust mixed-methods approach yields unique findings that enrich the existing literature on ICT and women’s empowerment.